2006
DOI: 10.1111/j.1365-2559.2005.02320.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of histopathology in establishing the diagnosis of tuberculous pericardial effusions in the presence of HIV

Abstract: Co-infection with HIV impacts on the histopathological features of pericardial tuberculosis and leads to a decrease in the sensitivity of the test. In areas which have a high prevalence of tuberculosis, the combination of a sensitive test such as adenosine deaminase, chest X-ray and clinical features has a higher diagnostic efficiency than pericardial biopsy in diagnosing tuberculous pericarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 34 publications
0
16
1
3
Order By: Relevance
“…This question is relevant because IL-13-secreting CD4 + T H 2 cells, which are reduced by HIV, regulate fibrogenesis directly, through stimulating collagen synthesis by fibroblasts and indirectly by promoting TGF-β1 production by macrophages [6]. Furthermore, fewer granulomata have been observed in HIV infected tuberculous pericarditis patients with severely depleted CD4 lymphocytes, suggesting that there may be less propensity to develop pericardial fibrosis in HIV-infected individuals with tuberculous pericardial effusion [7].…”
Section: Introductionmentioning
confidence: 99%
“…This question is relevant because IL-13-secreting CD4 + T H 2 cells, which are reduced by HIV, regulate fibrogenesis directly, through stimulating collagen synthesis by fibroblasts and indirectly by promoting TGF-β1 production by macrophages [6]. Furthermore, fewer granulomata have been observed in HIV infected tuberculous pericarditis patients with severely depleted CD4 lymphocytes, suggesting that there may be less propensity to develop pericardial fibrosis in HIV-infected individuals with tuberculous pericardial effusion [7].…”
Section: Introductionmentioning
confidence: 99%
“…16 Recent data suggest that the histological pattern is affected by the immune status of the patient, with fewer granulomas being observed in HIV-infected patients with severely depleted CD4 lymphocytes. 17 The lymphatic drainage of the pericardium is primarily to the anterior and posterior mediastinal and tracheobronchial lymph nodes and is reflected by the pattern of lymphadenopathy seen in tuberculous pericarditis. 18 The mediastinal node enlargement of tuberculous pericardial effusion is not visible on a routine chest radiograph but can be seen on CT or MRI.…”
Section: Pathogenesis Of Tuberculous Pericarditismentioning
confidence: 99%
“…This is illustrated in the IMPI registry34 35 that reported that across the continent, the diagnosis of tuberculous pericarditis was made at the clinical discretion of the attending physician in the majority of cases34 with few centres adopting a standardised diagnostic approach to establishing a definitive diagnosis. In addition, the performances of culture-based and smear-based tests for tuberculous pericarditis are compromised due to a paucibacillary pericardial fluid (even though it may be multibacillary in advanced HIV48) in a greater majority of the patients,50 while the accuracy of histological diagnostic are reduced in the context of HIV infection as fewer granulomas are observed in those with severe immunosuppression 51. With the high morbidity and mortality associated with tuberculous pericarditis, especially in persons living with HIV/AIDS, current efforts towards the development of a highly sensitive and/or specific test are solicited.…”
Section: Discussionmentioning
confidence: 99%